The Challenge of cerebral vascular diseases - Wright, Irving S. (Thrombosis and Haemostasis, 1957)
Cerebral vascular diseases are of major importance but unfortunately their study has been greatly neglected until recent years.There are serious gaps in our basic knowledge regarding their pathogenesis and therapy. The differential diagnoses of thrombosis, embolism, hemorrhage and tumor have been outlined. Intermittent neurological signs due to cerebral vascular diseases have been discussed. The distinctions between intermittent and permanent occlusion of the basilar artery, carotid artery and cerebral artery have been elaborated.Long term anticoagulant therapy is of value in the prevention of recurrent thromboses and emboli wherever they may occur in the carotid, basilar or cerebral arterial tree.Anticoagulants are indicated as a prophylactic measure before mitral com-misurotomy when the patient has had previous emboli or when his heart is in atrial fibrillation. They should also be continued after this surgery. The question whether the patient should be carried through the operation at therapeutic levels of anticoagulant therapy is at present under study in several clinics, but the evidence suggests that this is feasible and improves the chances of avoiding emboli.It appears logical to use anticoagulants in the treatment of acute episodes of thrombosis and embolism but this is under further study at present.Other forms of therapy including the stellate sympathetic ganglion block, and the inhalation of CO2 have been evaluated. Thus far the evidence suggests that while the inhalation of CO2 may be helpful theoretically the others are of doubtful value.This is a challenging field which should attract the attention of many workers during the next several decades.